POLITIK HUKUM UU NO 35 TAHUN 2009 TENTANG NAKOTIKA DALAM KAITANNYA DENGAN PERGESERAN PARADIGMA PEMIDANAAN BAGI PENGUNA/PECANDU DAN KORBAN NARKOTIKA - Sinaulan, Ramlani Lina (Jurnal Review Politik, 2016)
Politics, Law is a study subject in shaping the legal system in the form of legislation. Determining the shape of the Political Law should be based on the outlook of the nation’s philosophy (philosophie grond- slag). Thus, the output of a legislative process in the form of legisla- tion, particularly in criminal law, into the direction of and in line with the social life in the community.The behavior of law enforcement institutions, often overlooked in the study of Politics of Criminal Law. Thus, often the implementation of a legislation disoriented, disharmony and synchronized in the level of practice of law in Indonesia.